Bioensayo para la detección de PHYTOPHTHORA CINNAMOMI EN EL SUELO DE RODALES AFECTADOS POR LA SECA DE QUERCUS (III Congreso Forestal Español, 2001)
The isolation of Phytophthora spp. from soil samples is often difficult, even using indirect methods which combine baiting techniques and selective media. Apple or avocado fruits or carnation petals are some of the most common baits used for the isolation of P. cinnamomi from infested soils where Quercus ilex and Q. suber have been affected by root rot and decline. However, the use of these baits has serious limitations because of the contamination by several fungi and bacteria. The aim of this work was to improve the baiting technique for the pathosystem P. cinnamomi / Quercus spp. The effect of different factors, including several baits (leaves, fruits, cotyledons, radicles), the soil:water dilution, and the incubation time, was checked using a soil mixture artificially infested with several isolates of P. cinnamomi. The most effective baiting method included baits of eucalyptus phyllodium pieces (Eucalyptus globulus and less effective E. camaldulensis), 1:6 soil:water relation, and 4 days incubation period. The efficiency of this method has been tested for the detection of P. cinnamomi in naturally infested soil samples from fields where the root rot caused by this pathogen had been previously diagnosed

Etiología de las podredumbres radicales de plántulas de QUERCUS SPP. Y PINUS HALEPENSIS EN VIVEROS FORESTALES DE ANDALUCÍA (III Congreso Forestal Español, 2001)
A disease surey carried out during 1998-99 showed that holm oak (Quercus ilex) and Aleppo pine (Pinus halepensis) seedlings were affected by damping-off and root rot in three forest nurseries in Andalucía, southern Spain. A similar problem was detected affecting four species of Quercus (Q. coccinea, Q. faginea, Q. ilex, and Q. suber) in a forest nursery in 2000. Three species of Phytophthora (P. cinnamomi, P. cryptogea, and P. drechsleri) were isolated from holm oak feeder roots, and P. drechsleri was isolated from feeder roots of Aleppo pine in the first survey in 1998-99. In the second survey, Cylindrocarpon didymum was isolated from the feeder roots of the four Quercus spp. essayed, and C. destructans was isolated only from Q. faginea. Pathogenicity tests were conducted using 1 year-old healthy plants of cork oak, holm oak and Aleppo pine. Isolates of the three Phytophthora species were pathogenic to the three host species, inducing root rot and plant death. Holm oak was the most susceptible host and P. cinnamomi was the most virulent species. Isolates of Cylindrocarpon were pathogenic to cork oak and holm oak causing root rot, yellowing, defoliation, and plant death.

DETERMINACIÓN DE LOS RECURSOS ENERGÉTICOS QUE CUBREN LAS NECESIDADES ALIMENTICIAS EN SISTEMAS DE DEHESA1 DETERMINATION (Archivos de Zootecnia, 1996)
Dehesas are farming systems that covers with their own resources agreat deal of cattle food needs. However. the use and contribution of these resources haven"t a uniform distribution between the diferent stock species. This paper deals with an analytical case study of characteristic dehesas of SW Badajoz (Spain), where the factors that influence the use of grazing resources have been determinated. The analyzed dehesas cover up to 73 p.100 of food needs for ruminants, but only 47 p.100 for Iberian pig. The knowledge of food energetic flows is a solid starting point to analyze the management and the sustainable use of dehesa resources.